Coordinated In Vitro Release of Granulysin, Perforin and IFN-γ in TB and HIV/TB Co-Infection Associated with Clinical Outcomes before and after Anti-TB Treatment - Nada Pitabut (Pathogens, 2020)
Granule-associated killing molecules released from cytotoxic T lymphocytes participate as a crucial step in immunity against tuberculosis (TB), but the role of coordinated production remains controversial. Coordinated release of effector molecules in vitro after stimulating peripheral blood mononuclear cells (PBMCs) of active TB or HIV/TB coinfection patients with PPD, purified protein derivative of tuberculin and avirulent Mtb, H37Ra, an attenuated strain were investigated in association with clinical outcomes. Perforin, granzyme-B, granulysin and IFN-γ were measured using ELISA. Before anti-TB treatment, PBMCs of TB stimulated with PPD or H37Ra released higher perforin, granzyme-B, and granulysin levels than in HIV/TB and released significantly higher IFN-γ (p = 0.045, p = 0.022). Granulysin positively correlated with perforin in TB (p = 0.042, r = 0.385), HIV/TB coinfection (p = 0.003, r = 0.941) after PPD stimulation, and after H37Ra stimulation in TB (p = 0.005, r = 0.549), but negatively correlated with granzyme B in TB (p = 0.042, r = −0.386), HIV/TB coinfection (p = 0.042, r = 0.754) were noted. After anti-TB treatment, increased levels of perforin, granulysin and IFN-γ in TB or HIV/TB upon PPD or H37Ra stimulation, and decreased granzyme-B levels after PPD (p = 0.003) or H37Ra (p = 0.028) stimulation in TB were observed. These results suggest that granulysin may act synergistic with perforin and IFN-γ in TB, indicating its crucial function in host immunity to tuberculosis. Future studies with larger numbers of patients ought to be conducted in the future.